Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1016/j.neuroimage.2005.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation during execution and motor imagery of novel and skilled sequential hand movements

Abstract: This experiment used functional magnetic resonance imaging (fMRI) to compare functional neuroanatomy associated with executed and imagined hand movements in novel and skilled learning phases. We hypothesized that 1 week of intensive physical practice would strengthen the motor representation of a hand motor sequence and increase the similarity of functional neuroanatomy associated with executed and imagined hand movements. During fMRI scanning, a right-hand self-paced button press sequence was executed and ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
177
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(210 citation statements)
references
References 80 publications
26
177
0
7
Order By: Relevance
“…However, these differences dissipate when assessing imagery of more general motor skills, unrelated to their sport [10,12]. It has been demonstrated that intensive physical practice and subsequent improvement in the performance of a motor skill also alters the pattern of neural activation during motor imagery [13], and taken with our knowledge of the imagery ability of elite athletes, this indicates that task experience can influence imagery ability and accompanying neural activation. However, it is unclear whether the differences in activation in athletes compared to novice performers are related to the vividness of the motor images per se or that the changes in neural activation have occurred as a result of motor learning.…”
Section: Introductionmentioning
confidence: 99%
“…However, these differences dissipate when assessing imagery of more general motor skills, unrelated to their sport [10,12]. It has been demonstrated that intensive physical practice and subsequent improvement in the performance of a motor skill also alters the pattern of neural activation during motor imagery [13], and taken with our knowledge of the imagery ability of elite athletes, this indicates that task experience can influence imagery ability and accompanying neural activation. However, it is unclear whether the differences in activation in athletes compared to novice performers are related to the vividness of the motor images per se or that the changes in neural activation have occurred as a result of motor learning.…”
Section: Introductionmentioning
confidence: 99%
“…PascualLeone (2003) proved that mental practice has not only the capacity to improve performance it also changes the size of the cortical representation of the motor cortex over time. Motor imagery can improve the dynamics of motor performance (Yaguez et al, 1998) and the velocity and smoothness of sequential movements trajectories (Lacourse et al, 2005). Yet mental music rehearsal does not only include motor, kinesthetic and auditory imagery but also emotional aspects of the piece rehearsed, which involves three components: a semantic meaning component, a stimulus component and a response component that defines the imagined emotion (Lang, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we speculate that the role of action familiarity in modulation of the SMR is that individuals must have some experienced executing an action in order to perform motor imagery of that action reliably (see Olsson & Nyberg, 2010), but other factors, such as the complexity of the particular imagined action, determine how robust the brain response will be for that action. In fact, in studies of short-term motor learning, brain responses to motor imagery are enhanced following overt practice of novel actions (e.g., Lacourse et al, 2005;Baeck et al, 2012). For this reason, although this work only examined familiar imagery among highly experienced athletes and musicians, we propose that it is worthwhile to select an imagery task based on a person's skills and interests to attempt to ensure a reliable brain response during motor imagery, regardless of the person's level of expertise in executing the action.…”
Section: Discussionmentioning
confidence: 99%